Bronchopulmonary disease in coeliac patients. Issue 4 (April 1985) - Edwards, C; Williams, A; Asquith, P
Abstract : This paper describes the necropsy changes in a patient with coeliac disease and respiratory disease and the pulmonary biopsies from 13 other coeliac patients with physiological evidence of a parenchymal lung disorder. Postmortem examination showed partial fibrous obliteration of small airways and dilatation of larger airways, and the biopsies suggested similar changes in the other patients. We were unable to find any evidence of granulomatous or primary interstitial lung disease.